Prevalence, Clinical Features, and Management of Hydatid Disease in Saudi Arabia: Systematic Review - AL BRAIKAN, FATENA (Journal of King Abdulaziz University: Medical Sciences, 2024)
Hydatidosis, caused by Echinococcus granulosus, is an endemic parasitic disease worldwide. The most frequent anatomic locations are the liver and lung. This systematic review examined the prevalence, clinical features, diagnosis, and management of hydatid disease in Saudi Arabia. Six databases (PubMed, Medline, Ovid, Scopus, Web of Science, and Cochrane) were searched using the keywords “Hydatid AND Saudi Arabia” in the title and abstract. All papers investigating the hydatid diseases in Saudi Arabia were included in the systematic review. Eight articles were considered suitable for the systematic review of 82 papers that were extracted through the database search. The studies enrolled 835 patients, of whom 440 cases were diagnosed with hydatid disease. The prevalence of hydatid disease among patients with liver diseases ranged between 3.9 and 5.6% during the period from 1978 to 2014. In addition, the liver was the most reported infected organ with hydatid diseases, followed by the lungs among patients. Some studies diagnosed hydatid disease among asymptomatic patients, while others reported gastrointestinal, respiratory, and musculoskeletal symptoms. The most commonly reported diagnostic methods were indirect hemagglutination (IHA), ultrasonography, and Computed Tomography (CT) scans for locating cysts. A combined approach of surgical interventions such as endocystectomy and cystoperiocystectomy with medical therapy has shown greater effectiveness despite some associated complications like anaphylaxis, mild hypernatremia, biliary leakage, and bronchopleural fistula. Improving treatment outcomes and minimizing complications requires a multidisciplinary approach that combines surgical expertise with medical therapy, increased public awareness, and early diagnosis promotion.